2020
DOI: 10.1515/sjpain-2019-0144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral alcohol administration on heat pain threshold and ratings of supra-threshold stimuli

Abstract: Background and aimsEvidence for analgesic effects of oral alcohol consumption on heat pain has recently been documented in a placebo-controlled, randomized and double-blind design. We aimed at further investigating these effects and now set the focus on pain threshold and the ratings of supra-threshold pain to cover most of the pain range. Moreover, we now firstly evaluated sex differences in these effects.MethodsWe investigated 41 healthy participants (22 females) in a randomized, double-blind and placebo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Taken together, our findings are in line with recent literature supporting the analgesic properties of alcohol in producing clinically relevant reductions in ratings of pain intensity and increases in pain threshold (Capito et al, 2020; Thompson et al, 2017; Williams et al, 2021). Of note, there is limited prior research on the effects of acute alcohol intake on pain unpleasantness, with a single study demonstrating a statistically significant increase in pain unpleasantness under a lower alcohol dose (0.06%) and no significant changes under a moderate alcohol dose (0.08%) in response to heat pain stimuli (Capito et al, 2020). Given our use of pressure‐based pain stimuli in the present study, additional research is needed to determine whether mixed findings regarding pain unpleasantness depend on stimulus modality or other methodological differences (e.g., administration of both low and moderate alcohol doses).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our findings are in line with recent literature supporting the analgesic properties of alcohol in producing clinically relevant reductions in ratings of pain intensity and increases in pain threshold (Capito et al, 2020; Thompson et al, 2017; Williams et al, 2021). Of note, there is limited prior research on the effects of acute alcohol intake on pain unpleasantness, with a single study demonstrating a statistically significant increase in pain unpleasantness under a lower alcohol dose (0.06%) and no significant changes under a moderate alcohol dose (0.08%) in response to heat pain stimuli (Capito et al, 2020). Given our use of pressure‐based pain stimuli in the present study, additional research is needed to determine whether mixed findings regarding pain unpleasantness depend on stimulus modality or other methodological differences (e.g., administration of both low and moderate alcohol doses).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a moderate alcohol intake has been reported to exert analgesic effects. A randomized, double-blind, and placebo-controlled intervention study on healthy adults by Capito et al [ 10 ] demonstrated that low doses of alcohol were particularly effective for analgesia. As an underlying mechanism for the analgesic effects of alcohol intake, Lovinger and Roberto [ 11 ] considered a decrease in excitatory neurotransmission due to the rapid inhibition of the ionotropic glutamate receptor activity of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between alcohol intake and CP, previous studies have demonstrated that neuropathic pain due to an excessive alcohol intake [ 6 , 7 ], biogenic amines present in alcohol [ 8 ], or increased blood serotonin levels after drinking [ 9 ] may trigger headaches. However, moderate drinking has been shown to exert analgesic effects [ 10 , 11 , 12 ]. Therefore, the relationship between alcohol intake and CP has not yet been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, reward loss also induces a reduced sensitivity to nociceptive-pain (hypoalgesia) which appears to reflect activation of a compensatory opioid and cannabinoid system to modulate physical and psychological pain as a component of homeostatic and allostatic modifications [ 74 ]. It is clear that low or moderate amounts of consumed alcohol also exerts clinically relevant hypoalgesic effects in controlled experimental studies with people and animals [ 50 , 55 , 56 , 139 ]. Similar effects of alcohol and endogenous opioids on nociceptive-pain suggest an intersection of neural circuits, more specifically the opioid-mediated regulation of GABA neurotransmission [ 109 , 140 ].…”
Section: Self-medication With Alcoholmentioning
confidence: 99%